Mammographic breast density and cardiovascular disease in women. A literature review - E. V. Bochkareva; N. I. Rozhkova; E. K. Butina E. K; I. V. Kim; O. V. Molchanova; S. Yu. Mikushin; P. V. Ipatov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2024)
The world is searching for new simple and economically available gender-specific markers to improve cardiovascular risk stratification in women. The aim of this review was to analyze the association of mammographic density (MD) with cardiovascular disease (CVD). In low MD, i.e., high relative mammary gland fat content, there is a higher incidence of the main risk factors for CVD: hypertension, hyperlipidemia, hyperglycemia, excess body weight, as well as an increase in the volume of fat depots, visceral and ectopic fat. Low MD is associated with a higher 10-year risk of adverse cardiovascular events such as coronary artery disease, stroke, peripheral arterial disease, revascularization, and heart failure, and may serve as a predictor of their development. Including MD in the Framingham Risk Score model improves its accuracy. Identification of low MD, as a marker of high cardiovascular risk, allows the use of mammography for early detection and prevention of the two most dangerous diseases among the female population — breast cancer and CVD.